SARS-CoV-2 Genomic Surveillance from Community-Distributed Rapid Antigen Tests, Wisconsin, USA - Isla E. Emmen; William C. Vuyk; Andrew J. Lail; Sydney Wolf; Eli J. O’Connor; Rhea Dalvie; Maansi Bhasin; Aanya Virdi; Caroline White; Nura R. Hassan; Alex Richardson; Grace VanSleet; et al. (Emerging Infectious Diseases)
In the United States, SARS-CoV-2 genomic surveillance initially relied almost entirely on residual diagnostic specimens from nucleic acid amplification–based tests. However, use of those tests waned after the end of the COVID-19 Public Health Emergency on May 11, 2023. In Dane County, Wisconsin, we partnered with local- and state-level public health agencies and the South Central Library System to continue genomic surveillance by obtaining SARS-CoV-2 genome sequences from freely available community rapid antigen tests (RATs). During August 15, 2023–February 29, 2024, we received 227 RAT samples, from which we generated 127 sequences with >10× depth of coverage for >90% of the SARS-CoV-2 genome. In a subset of tests, lower cycle threshold values correlated with sequence success. Our results demonstrated that collecting and sequencing results from RATs in partnership with community sites is a practical approach for sustaining SARS-CoV-2 genomic surveillance.